Telling tales: Management gurus' narratives and the construction of managerial identity - CLARK, Timothy Adrian Robert (Institutional Knowledge at Singapore Management University, 1998)
This paper examines the reasons for the apparently powerful impact of management gurus' ideas (i.e. guru theory) on senior managers. An examination of the limited literature on management gurus and other related literatures suggests three explanations for the appeal of guru theory for senior managers. The first set of explanations relates to various features of management work which may heighten managers' receptivity to guru ideas. The second set focuses on the gurus themselves and emphasizes the form in which they are presented (i.e. public performances). The final set of explanations highlights the importance of the socioeconomic and cultural context within which guru theories emerge and become widely adopted. A number of criticisms of these explanations are offered: that they define the manager as passive, that the flow of ideas is one way (guru to manager), that they rely on an academic conception of knowledge. An alternative explanation of their success is outlined which suggests that their work – their analyses, presentations and theories – offer attractive conceptions of the role of managers which constitute the identity of the modern senior manager as an heroic, transformative leader. Gurus therefore not only constitute the organizational realities but also managers themselves.